IMPLEMENTASI TIA-942 PADA PEMBANGUNAN RUANG SERVER (STUDI KASUS : UPT SIMJAR STMIK STIKOM INDONESIA) - I Dewa Putu Gede Wiyata Putra; Made Dona Wahyu Aristana (Jurnal Teknologi Informasi dan Komputer, 2022)
ABSTRACTThe data center is a facility that centralizes an organization's shared IT operations and equipment to store, processing, and disseminate data and applications. UPT SIMJAR is a technical implementing unit that functions in the field of data management technology and information system technology services at STMIK STIKOM Indonesia. The data center of UPT SIMJAR has a small computer room size, without a backup power supply, room construction, and security systems that are not yet ideal. As a result of these conditions the process of service activities to be disrupted. Implementation of the data center design was carried out into a server room according to the TIA 942 standard. The results of this study standardized data centers that met the criteria of availability, scalability/flexibility, and security.Keywords: data center, tier, TIA, ruang serverABSTRAKData center adalah sebuah ruangan yang digunakan untuk menyimpan server dan perangkat jaringan. UPT SIMJAR merupakan unit pelaksana teknis yang berfungsi di bidang teknologi pengelolaan data dan pelayanan teknologi sistem informasi kepada seluruh civitas akademik di STMIK STIKOM Indonesia. Data center UPT SIMJAR memiliki ukuran computer room yang kecil, tanpa backup power supply, konstruksi ruang dan sistem keamanan yang belum ideal. Akibat dari kondisi tersebut membuat proses kegiatan pelayanan menjadi terganggu. Dalam penelitian ini dilakukan implementasi rancangan data center tersebut menjadi sebuah ruang server yang sesuai standar TIA 942. Hasil dari penelitian ini standarisasi data center yang memenuhi kriteria availability, scalability/flexibility dan security.Keywords: data center, tier, TIA, ruang server